‘Invisible schools’. The public image of rural schools in Southern Italy in photographic inquiries and photo-reportages (1925-55) - Meda, Juri (Historia y Memoria de la Educación, 2018)
The dissemination of a particular public image of rural schools ―ever since the poorest and most disadvantaged schools― has frequently been used by the ruling classes and / or political parties to document the rate of modernity and/or backwardness of the national school system, depending on the respective propaganda needs. Moving from the first photographic surveys conducted in Southern Italy in 1920s by the associations engaged in the socio-economic integration of the South into the Unitary State to get to the photo reportages published in some magazines in the 1950s, the article analyses in depth the manipulation of the public image of these particular schools as it emerges by the circulation of such photographs on daily newspapers and magazines, which reveals its propagandistic use over time.